Effect of Internal Control System on the Prevention of Fraud in the Central Bank of Nigeria - Kanu, Ndubuisi Ogbonnaya; Ugwudioha, Ofili; Azu, Nnanna P. (International Journal of Economics and Financial Issues, 2025)
This study examines the effect of internal control systems on fraud prevention in the Central Bank of Nigeria (CBN), with particular focus on the moderating role of emotional intelligence (EI). Using the COSO internal control framework, the research assessed five components—control environment, risk assessment, control activities, information and communication, and monitoring activities—to determine their effectiveness in curbing fraud. A quantitative cross-sectional survey was conducted among 458 purposively selected CBN staff, yielding 401 valid responses. Data were analysed using multiple regression, including interaction terms to evaluate the influence of EI. Findings revealed that monitoring activities and risk assessment had statistically significant positive effects on fraud prevention, while control environment and control activities did not. Notably, emotional intelligence significantly moderated the relationship between risk assessment and fraud prevention, indicating that emotionally intelligent personnel strengthen fraud control outcomes. The study underscores the strategic value of emotional intelligence in enhancing proactive fraud control mechanisms. It recommends embedding EI training into staff development, especially in high-risk operational areas, and calls for reforms in internal control policies to focus on data-driven, risk-sensitive monitoring systems. These insights are crucial for improving fraud risk governance and ensuring financial integrity within public financial institutions like the CBN.